2016
DOI: 10.1037/tra0000134
|View full text |Cite
|
Sign up to set email alerts
|

The effect of childhood emotional maltreatment on romantic relationships in young adulthood: A double mediation model involving self-criticism and attachment.

Abstract: Understanding the long-term psychological dynamics related to CEM and identifying mediating vulnerability factors-self-criticism and attachment avoidance-might have implications for both the assessment and treatment of individuals with a history of CEM, particularly as effective interventions to address self-criticism and attachment issues are available. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
(122 reference statements)
1
18
0
1
Order By: Relevance
“…emotional abuse) and psychopathology (Carvalho, Sousa, Da Motta, & Cabral, 2019;Crapolicchio, Vezzali, & Regalia, 2020;Naismith et al, 2019). For instance, Lassri, Luyten, Cohen, and Shahar (2016) found DSO symptoms such as interpersonal difficulties were linked to a history of ACEs through self-criticism. Being one of the most common symptoms in people with ACEs, self-criticism can stimulate stress response, leading to more CPTSD symptoms (Feinson & Hornik-Lurie, 2016;Lassri, Luyten, Fonagy, & Shahar, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…emotional abuse) and psychopathology (Carvalho, Sousa, Da Motta, & Cabral, 2019;Crapolicchio, Vezzali, & Regalia, 2020;Naismith et al, 2019). For instance, Lassri, Luyten, Cohen, and Shahar (2016) found DSO symptoms such as interpersonal difficulties were linked to a history of ACEs through self-criticism. Being one of the most common symptoms in people with ACEs, self-criticism can stimulate stress response, leading to more CPTSD symptoms (Feinson & Hornik-Lurie, 2016;Lassri, Luyten, Fonagy, & Shahar, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that explore individual differences in relation to maltreatment using the childhood trauma questionnaire (CTQ) as a continuous score, have reported a positive association between internalizing symptoms (e.g., Herringa et al 2013 ; Huh et al 2017 ), emotion dysregulation and psychopathology (Jennissen et al 2016 ; Peh et al 2017 ). In addition, a study examining the effect of emotional abuse and neglect on a continuum has found a positive relation with internalizing symptoms (Hamilton et al 2013 ) and another exploring the continuous effect of the combined score of emotional abuse and neglect found that self-criticism mediated the link between emotional abuse and neglect and romantic satisfaction (Lassri et al 2016 ).…”
Section: Neglect and Internalizing Symptomsmentioning
confidence: 99%
“…Além disso, também entrou, nessa categoria, o relato de jovens que compartilharam sobre os padrões transgeracionais afetivos de seus familiares. Desse modo, oito estudos internacionais que integraram o corpus de análise buscaram investigar as dimensões do apego adulto estabelecidas com a família de origem, que pudessem estar relacionadas com projetos de vida (Chopik, Edelstein, & Grimm, 2017;Fraley, Roisman, Booth-laforce, Owen, & Holland, 2013;Lantagne e Furman, 2017;Lassri, Luyten, Cohen, & Shahar, 2016;Lopez et al, 2013;Simons et al, 2014;Sun, Wang, & Jiang, 2017;Zaman & Fivush, 2013). A fim de facilitar a compreensão das temáticas contempladas nessa categoria, foram desmembrados os seguintes subtemas que compuseram a análise: desenvolvimento do apego ao longo do ciclo vital (n=5); padrões transgeracionais do apego nas relações familiares (n=2); violência infantil e apego adulto (n=1).…”
Section: Apego Adultounclassified